A Selective Ink Deposition Method for the Cost-Performance Optimization of Inkjet-Printed UHF RFID Tag Antennas. (17th May 2012) - Virtanen, J.; Virkki, J.; Elsherbeni, A. Z.; Sydänheimo, L.; Ukkonen, L.
Abstract : A selective ink deposition method is proposed for fabricating inkjet-printed passive UHF RFID tag antennas with optimized cost-performance ratios. The deposition method is based on identifying areas with high surface current densities on a given tag antenna and applying additional silver nanoparticle ink onto such areas to increase tag read range. In this paper, the proposed method is experimentally verified by utilizing the method on a small dipole tag antenna. Several ink deposition schemes are created, and their read range performances and ink consumptions are presented.